2006
DOI: 10.1002/rcm.2680
|View full text |Cite
|
Sign up to set email alerts
|

Desorption sonic spray ionization for (high) voltage‐free ambient mass spectrometry

Abstract: Sonic spray ionization is shown to create a supersonic cloud of charged droplets able to promote efficient desorption and ionization of drugs directly from the surfaces of commercial drug tablets at ambient conditions. Compared with desorption electrospray ionization (DESI), desorption sonic spray ionization (DeSSI) is advantageous since it uses neither heating nor high voltages at the spray capillary. DeSSI therefore provides a more friendly environment in which to perform ambient mass spectrometry (MS). DeSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
295
0
12

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(316 citation statements)
references
References 16 publications
9
295
0
12
Order By: Relevance
“…EASI, which was originally termed DeSSI [32], is one of the simplest, gentlest and most easily implemented ionization methods. EASI uses super-sonic-spray ionization to create minute droplets which become charged due to statistical imbalance distribution of charge (cations and anions).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…EASI, which was originally termed DeSSI [32], is one of the simplest, gentlest and most easily implemented ionization methods. EASI uses super-sonic-spray ionization to create minute droplets which become charged due to statistical imbalance distribution of charge (cations and anions).…”
Section: Introductionmentioning
confidence: 99%
“…EASI displays, therefore, several unique features: requires no voltage to eliminate counter-ions, no voltage switches from positive to negative ion modes and vice-versa, no heating for desolvation and is less prone to analyte oxidation. Comparisons of EASI and DESI for the same sample [32] showed that there were less background cluster ions from solvent ionization (noise) and in some cases higher abundance of the analyte ions in the spectrum, when EASI was used. Otherwise the EASI-MS data are quite similar to ESI-MS or SSI-MS data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In DESI, high-speed electrically charged drop-lets directly sprayed onto the sample surface and secondary ions would be generated during the process of surface collisions [5][6][7]. A similar technique related to DESI, where the solution was sprayed with very highspeed nebulization auxiliary gas but no voltage applied, is called desorption sonic spray ionization (DeSSI) [8] or easy ambient sonic-spray ionization (EASI) [9]. There are several other two-step techniques of coupling laser desorption and ESI.…”
mentioning
confidence: 99%
“…Recently, breakthrough of mass [36,37]. After DESI, more than 20 ambient ionization techniques were further developed, including direct analysis in real time (DART) [38,39], surface desorption atmospheric pressure chemical ionization (DAPCI) [40,41], extractive electrospray ionization (EESI) [42], low temperature plasma (LTP) [43,44], and easy ambient sonic ionization (EASI) [45]. Two major advantages of ambient mass spectrometry are minimal sample pre-treatment and high-throughput MS analysis [46][47][48].…”
Section: Introductionmentioning
confidence: 99%